The results of deep seismic studies using OGT, DGS and MOVZ methods of Onega-Ladozhskaya area (Republic of Karelia, Russia) - N. V. Sharov; E. V. Isanina; N. G. Zamozhnyaya; N. A. Krupnov; A. K. Suleimanov (Геофизический журнал, 2011)
The results of the CDP, DSS, ECWM regional seismic and seismotomographic study of the Onega-Ladoga area, conducted in 1975-2002, are reviewed. Combined multi-wave studies are carried out to reveal the essential details of the deep structure of the earth crust and to understand the nature of their seismic heterogeneity better. The above methods add to each other. Based on DSS data, the velocity pattern of the crust and its blocks was elucidated and M-dis-continuity was traced. Based on CDP data, inclined boundaries were located and correlated with geological structures. ECW sections characterize geo-space both statistically (the position and number of boundaries, fault zones and blocky pattern), and dynamically (the tension and rigidity of contacts and fracturing). Seismic parameters are shown to be related to the geological structure of individual crustal blocks. The crust is 35-50 km thick.